Farmer’s participatory sodic soil reclamation programme improved livelihood of resource poor farmers - Singh, Y P; Mishra, V K; Arora, S; Sharma, P C (Indian Farming, 2019)
Land degradation due to the accumulation of salts in the soil is an alarming threat to agricultural productivity and sustainability, particularly in arid and semiarid regions of the world. In India, about 6.73 million ha soils are salt affected which represents 2.1% of the geographical area of the country. Out of these, 2.8 million ha are sodic and mainly occur in the alluvial soils of the Indo-Gangetic plains (IGP) and a large proportion of these soils are cultivated by smallholder farmers, who rely on that piece of land to satisfy their food and feed needs. High pH and exchangeable sodium content, and presence of soluble carbonate and bicarbonate, not only adversely affect the physico-chemical properties of the soils, but also profoundly influence the soil biological conditions. There are many approaches to reclaim sodic soils like chemical reclamation and phytoremediation. Under chemical amelioration, gypsum (CaSO4.2H2O) has been used most extensively but it is costly (US $50/t) and beyond the reach of small and marginal farmers because it is require in large quantity (12-16 t/ha) which contributes about 60% of the total reclamation cost. Pressmud, a sugar industry by-product, is readily available and less expensive than gypsum is one organic amendment, which can be used to improve the physical, chemical and biological properties of sodic soils, because it contains sizable quantities of macro-and micro-nutrients, high calcium sulphate and organic matter contents.